2013
DOI: 10.1007/s13361-013-0606-0
|View full text |Cite
|
Sign up to set email alerts
|

Cation Recombination Energy/Coulomb Repulsion Effects in ETD/ECD as Revealed by Variation of Charge per Residue at Fixed Total Charge

Abstract: Electron capture dissociation (ECD) and electron transfer dissociation (ETD) experiments in electrodynamic ion traps operated in the presence of a bath gas in the 1–10 mTorr range have been conducted on a common set of doubly protonated model peptides of the form X(AG)nX (X = lysine, arginine, or histidine, n=1, 2, or 4). The partitioning of reaction products was measured using thermal electrons, anions of azobenzene, and anions of 1,3-dinitrobenzene as reagents. Variation of n alters the charge per residue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 73 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…In the Cornell mechanism, it is also assumed, given the significant (∼6 eV) energy released as the electron is initially captured in a high‐ n Rydberg state, that dissociation occurs before this energy can be redistributed among the ion's vibrational degrees of freedom (similar to UVPD or SID, described previously). This non‐ergodic mechanism is still often cited; however, several alternatives have been proposed over the years.…”
Section: Mechanism(s) Of Electron‐based Dissociation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Cornell mechanism, it is also assumed, given the significant (∼6 eV) energy released as the electron is initially captured in a high‐ n Rydberg state, that dissociation occurs before this energy can be redistributed among the ion's vibrational degrees of freedom (similar to UVPD or SID, described previously). This non‐ergodic mechanism is still often cited; however, several alternatives have been proposed over the years.…”
Section: Mechanism(s) Of Electron‐based Dissociation Methodsmentioning
confidence: 99%
“…In this type of experiment, the radical anion, rather than a cathode, serves as a source of low‐energy electrons, and this technique is, therefore, known as electron‐transfer dissociation . ECD and ETD are largely comparable, although it has been suggested that differences in internal energy and angular momentum transfer could lead to a slightly different branching ratio between available reaction pathways . Additionally, the presence of the anion introduces an additional reaction pathway not available in ECD; namely, transfer of a proton from the protein/peptide to the ETD reagent .…”
Section: Mechanism(s) Of Electron‐based Dissociation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These clear distinctions are based, in part, by our instrument's ability to perform Bhot ECD^(i.e., using electron energies in excess of 3 eV) [38,39] to generate fragment ions efficiently for these glycopeptides. This capability to tune electron energies makes ECD more useful than ETD, especially for doubly charged precursors [23], given that the energetics of those dissociation reactions are dictated by the specific chemical properties of the individual reagent ion employed [40], the reaction kinetics are hampered by the relatively small total number of charges involved in this ion/ion reaction [24], and compensating for these slow kinetics by using Bsupplemental activation^with ETD often results in the loss of the glycan moiety via that activation method [23].…”
Section: Dms-separated Glycopeptide Isomers Yield Informative Cid Andmentioning
confidence: 99%
“…McLuckey and coworkers have recently investigated the effect of recombination energy by comparing ECD spectra of small peptides to those from electron transfer dissociation (ETD), in which the recombination energy should be smaller than in ECD by the electron affinity of the reagent used, 0.6 eV for azobenzene and 1.7 eV for 1,3-dinitrobenzene [ 55 ]. Data interpretation was complicated by the fact that products from sequential electron transfer and H • loss could not be distinguished from products from competitive proton transfer.…”
Section: Excess Energy In Ecdmentioning
confidence: 99%